Dividends, Dilution, and Taxes: A Signalling Equilibrium - John, Kose; Williams, Joseph (Journal of Finance, 1985)
A signalling equilibrium with taxable dividends is identified. In this equilibrium, corporate insiders with more valuable private information optimally distribute larger dividends and receive higher prices for their stock whenever the demand for cash by both their firm and its current stockholders exceeds its internal supply of cash. In equilibrium, many firms distribute dividends and simultaneously issue new stock, while other firms pay no dividends. Because dividends reveal all private information not conveyed by corporate audits, current stockholders capture in equilibrium all economic rents net of dissipative signalling costs. Both the announcement effect and the relationship between dividends and cum-dividend market values are derived explicitly.